2023
DOI: 10.1038/s41467-023-36522-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized mitochondrial DNA induces gasdermin D oligomerization in systemic lupus erythematosus

Abstract: Although extracellular DNA is known to form immune complexes (ICs) with autoantibodies in systemic lupus erythematosus (SLE), the mechanisms leading to the release of DNA from cells remain poorly characterized. Here, we show that the pore-forming protein, gasdermin D (GSDMD), is required for nuclear DNA and mitochondrial DNA (mtDNA) release from neutrophils and lytic cell death following ex vivo stimulation with serum from patients with SLE and IFN-γ. Mechanistically, the activation of FcγR downregulated Serpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 74 publications
0
41
0
Order By: Relevance
“…Although NETs are mainly composed of chromosomal DNA, successive work showed mtDNA could be released with NETs in lupus-like disease [19,31], suggesting a direct involvement of mtDNA in NETs formation. Previous study has con rmed that cell-free mtDNA triggers NETs formation by TLR9 pathway during lung transplantation [7] and by cGAS-STING pathway in sickle cell disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although NETs are mainly composed of chromosomal DNA, successive work showed mtDNA could be released with NETs in lupus-like disease [19,31], suggesting a direct involvement of mtDNA in NETs formation. Previous study has con rmed that cell-free mtDNA triggers NETs formation by TLR9 pathway during lung transplantation [7] and by cGAS-STING pathway in sickle cell disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…4N) and the opening of mitochondrial permeability transition pore (mPTP) (Fig. 5D), allows for easier release of oxidatively damaged mtDNA into the cytoplasm (42)(43)(44). To date, several pathways including BAX/BAK macropore (43), mPTP (42), and N-terminal gasdermin D (GSDMD-N) (45) have been reported to be involved in the release of mtDNA.…”
Section: Midrs Damages Mitochondria To Activate Cytoplasmic Dna Sensorsmentioning
confidence: 99%
“…Gasdermin D (GSDMD), a pore-forming protein, has been shown to promote NETs formation [10,11]. A recent study demonstrated that oxidation of mtDNA (Ox-mtDNA) promotes GSDMD-N oligomerization and cell death in neutrophils in SLE [12 ▪ ]. Notably, Ox-mtDNA is essential for GSDMD-N oligomerization and subsequent cell death [12 ▪ ].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…A recent study demonstrated that oxidation of mtDNA (Ox-mtDNA) promotes GSDMD-N oligomerization and cell death in neutrophils in SLE [12 ▪ ]. Notably, Ox-mtDNA is essential for GSDMD-N oligomerization and subsequent cell death [12 ▪ ]. Therefore, the interaction between Ox-mtDNA and GSDMD establishes a positive feedback loop, ensuring the release of extracellular DNA and pro-inflammatory programmed cell death (PCD) in neutrophils in SLE.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%